2012
DOI: 10.1063/1.3675464
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Hall plateau−plateau transition in top-gated epitaxial graphene grown on SiC (0001)

Abstract: We investigate the low-temperature magneto-transport properties of monolayer epitaxial graphene films formed on the Si-face of semi-insulating 4H-SiC substrates by a high temperature sublimation process. A high-k top-gate on the epitaxial graphene is realized by inserting a fully oxidized nanometer thin aluminum film as a seeding layer, followed by an atomic layer deposition process. At low temperatures, the devices demonstrate a strong field effect by the top gate with an on/off ratio of ~7 and an electron mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
2
16
1
1
Order By: Relevance
“…(11)- (13) are not determined by the graph-theoretic data for the corresponding digraph (even in the simplest case of the critical point in the isotropic system). Therefore, it seems that an explicit calculation of S(p) for a given picture p is a much more challenging problem than that for |F (p)|.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11)- (13) are not determined by the graph-theoretic data for the corresponding digraph (even in the simplest case of the critical point in the isotropic system). Therefore, it seems that an explicit calculation of S(p) for a given picture p is a much more challenging problem than that for |F (p)|.…”
Section: Discussionmentioning
confidence: 99%
“…A famous example is the integer quantum Hall (IQH) plateau transition observed in two-dimensional (2D) semiconductor devices subject to strong magnetic fields. The nature of the critical state at and the critical phenomena near the IQH transition are at the focus of intense experimental [8][9][10][11][12][13] and theoretical research. [14][15][16][17][18][19][20][21][22][23] In spite of much effort over several decades, an analytical treatment of most of the critical conducting states in disordered electronic systems, including in particular that of the mentioned IQH transition, has been elusive (although some proposals [14][15][16] have been put forward, but see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Both techniques recently achieved at wafer scale mobility and uniformity levels comparable to those of exfoliated graphene. 8,9 As a major drawback, graphene produced by CVD must be transferred onto an insulating substrate for its use in electronics applications. On the contrary, the SiC substrate is insulating, and this in principle offers a clear technological advantage over other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the relativistic quantization of graphene's electronic spectrum results in distinct characteristics, including the presence of a Landau level (LL) at zero energy and chiral QHE. [8][9][10][11][12] In the quantum Hall (QH) regime, the plateau-plateau transition and the scaling behavior have been studied using Hall bar [13][14][15][16][17][18] and Corbino geometry, 19 providing important information about the carrier localization in graphene. A scaling exponent for typical Anderson-type transition κ ≅ 0.42 has been reported in graphene, 13,14 while some studies showed reduced value of κ .…”
mentioning
confidence: 99%
“…[8][9][10][11][12] In the quantum Hall (QH) regime, the plateau-plateau transition and the scaling behavior have been studied using Hall bar [13][14][15][16][17][18] and Corbino geometry, 19 providing important information about the carrier localization in graphene. A scaling exponent for typical Anderson-type transition κ ≅ 0.42 has been reported in graphene, 13,14 while some studies showed reduced value of κ . [15][16][17][18][19] In a graphene Hall bar, the slope of the Hall conductivity at the transition region, d / , exhibits scaling behavior with κ = 0.41 for the first and second LLs, while that of the zeroth LL is temperature (T) independent.…”
mentioning
confidence: 99%